2020
DOI: 10.1016/j.trf.2020.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Do drivers differ in their attitudes on speed limit compliance between work and private settings? Results from a group of Nigerian drivers

Abstract: Existing evidence suggests that drivers, particularly those who work in companies with strong road safety cultures exhibit different sets of speeding attitudes and behaviours in work and private driving. Using Ajzen and Fishbein's (1980) Theory of Planned behaviour (TPB) and onroad driving experiments, this study examined the self-reported and objective behaviour of driving within posted speed limits for a sample of fleet drivers. The findings show that the TPB explained up to 24% of the variance in intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…A significant and robust relationship was observed between speeding behaviour and both speeding intention and perceived behavioural control, which aligns with previous studies [10,11,29,30].These results suggest that modifying drivers' speeding intentions and their perception of control over speeding can have a substantial impact on their actual speeding behaviour. However, it is important to acknowledge the negative relationship between speeding behaviour and perceived behavioural control, which is in line with the findings of other authors [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A significant and robust relationship was observed between speeding behaviour and both speeding intention and perceived behavioural control, which aligns with previous studies [10,11,29,30].These results suggest that modifying drivers' speeding intentions and their perception of control over speeding can have a substantial impact on their actual speeding behaviour. However, it is important to acknowledge the negative relationship between speeding behaviour and perceived behavioural control, which is in line with the findings of other authors [11].…”
Section: Discussionsupporting
confidence: 89%
“…The theory of planned behaviour (TPB) postulated by Ajzen (1985Ajzen ( , 1991 has often been used by several researchers to study the speeding behaviour of drivers [6,[8][9][10][11][12] . The TPB studies factors that affect a behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ge et al [8] found that female drivers were significantly more careful than men, but in the study of Qaid et al [9], the driving behavior of women and men is not significantly different. Research on driving behavior above the speed limit has been widely carried out To reduce traffic accidents and fatalities, in which most of the research uses the theory of planned behavior (TPB) model; such as research [9], [17], [18]. Jovanović et al [18] Investigated insights in TPB models to predict driving behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Jovanović et al [18] Investigated insights in TPB models to predict driving behavior. Etika et al [17] used the TPB model to examine compliance with speed limits at work and outside work. While Qaid et al [9] used the TPB model to predict the intention to drive over the speed limit and its intervention.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the Theory of planned behavior has been successfully applied to predict various traffic violations, such as fatigue driving [15], driving while distracted by smartphones [16][17][18], and speeding [19,20]. A study on speeding behavior revealed that TPB informs 47% of behavioral changes among drivers [21].…”
Section: Introductionmentioning
confidence: 99%